THE EFFECT OF SPIRITUAL INTELLIGENCE AND EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF AUDITORS MODERATED BY REMUNERATION IN THE REGIONAL OFFICE OF DGT SPECIAL REGION OF YOGYAKARTA - Husadari, Daning; Priyastiwi, Priyastiwi; Tjahjono, Achmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze the influence of spiritual intelligence, emotional intelligence, and remuneration on the performance of tax auditors in the DGT Regional Office of the Special Region of Yogyakarta, as well as to evaluate the role of remuneration moderation in the relationship between spiritual intelligence and emotional intelligence on auditor performance. The method used in this study is quantitative descriptive with a population of 105 tax auditor employees in the DGT Regional Office of the Special Region of Yogyakarta, where the entire population is sampled using the saturated sample method, which is to make the entire population part of the sample. Data collection was carried out through questionnaires, and data analysis using a structural equation model (Structural Equation Model). The results of the study show that spiritual intelligence and emotional intelligence have a positive effect on the performance of tax auditors. In addition, remuneration also has a positive effect on the performance of tax auditors and acts as a moderation variable that strengthens the relationship between spiritual intelligence and emotional intelligence to the performance of tax auditors.